Existence and multiplicity of solutions for some Steklov problem involving (p1(x), p2(x))-Laplacian operator. Issue 3 (11th February 2023) - Chammem, Rym; Sahbani, Abdelhakim
ABSTRACT: In this paper, we study the existence and multiplicity of weak solutions to a ( p 1 ( x ) ; p 2 ( x ) ) -Laplacian problem. By means of variational methods, mountain pass lemma and its Z 2 symmetric version, we establish the existence and multiplicity of solutions.